\(x^2-2xy-3y^2=3x-y+2\)
\(\Leftrightarrow x^2-2xy-3x-3y^2+y-2=0\)
\(\Leftrightarrow x^2-x\left(2y+3\right)-3y^2+y-2=0\)
\(\Leftrightarrow4x^2-4x\left(2y+3\right)+\left(2y+3\right)^2-\left(2y+3\right)^2-12y^2+4y-8=0\)
\(\Leftrightarrow\left(2x-2y-3\right)^2-4y^2-12y-9-12y^2+4y-8=0\)
\(\Leftrightarrow\left(2x-2y-3\right)^2-16y^2-8y-17=0\)
\(\Leftrightarrow\left(2x-2y-3\right)^2-\left(16y^2+8y+1\right)=16\)
\(\Leftrightarrow\left(2x-2y-3\right)^2-\left(4y+1\right)^2=16\)
\(\Leftrightarrow\left(2x-6y-4\right)\left(2x+2y-2\right)=16\)
\(\Leftrightarrow\left(x-3y-2\right)\left(x+y-2\right)=4\)
Đến đây bn tự giải nha